Integration of Point of Care Ultrasound into an existing undergraduate medicine anatomy course - Sheppard, G; Harris, J; Hutchings, C; Wadman-Scanlan, H; Collins, P (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2025)
Implication StatementUltrasonography has become a valuable procedural guide and diagnostic tool across many medical specialties. A 2017 descriptive cross-sectional survey at Memorial University of Newfoundland found that there was support to integrate preclinical and clinical applications of point of care ultrasound (POCUS) into the undergraduate medical anatomy curriculum. Unlike previous studies that have focused on scanning a single body system, our group utilized a station-based model that allowed medical students to scan several different body systems throughout the year. Our experience in creating the syllabus, collecting feedback, and creating multiple choice assessment questions will be useful to other educators who may wish to integrate POCUS into their curriculum.